Enhanced Mechanical Properties and Oxidation Resistance of Zirconium Diboride Ceramics via Grain‐Refining and Dislocation Regulation. Issue 6 (2nd January 2022) - Xu, Haiyue; Ji, Wei; Guo, Weiming; Li, Yulin; Zou, Ji; Wang, Weimin; Fu, Zhengyi
Abstract: Zirconium diboride (ZrB2 ) is considered as one of the most promising ultra‐high temperature materials for the applications in extreme environments. However, the difficulty in fabrication of ZrB2 limits its industrial applications. In this study, fully dense and grain‐refined ZrB2 is prepared under ultra‐high pressure of 15 GPa at low temperature of 1450 °C. The as‐prepared ZrB2 exhibits excellent mechanical and oxidation‐resistant properties. Compared with raw powder, the grain size decreases 56%. Compared with high‐temperature sintered control specimen beyond 2000 °C, the hardness and fracture toughness increase about 46% and 69%, respectively, the dislocation density increase 3 orders of magnitude, while the grain size considerably decrease 96%. According to work hardening, Hall–Petch and Taylor dislocation hardening effects, the refined grains, substructures, and high dislocation density caused by plastic deformation during sintering can enhance the mechanical properties. The unique structure contributes to a threshold oxidation temperature increase of ≈250 °C relative to the high‐temperature sintered ZrB2, achieving one of the highest values (1100 °C) among the reported monolithic ultra‐high temperature ceramics. A developed densification mechanism of dislocation multiplication with grain refining is proposed and proved to dominate the sintering, which is responsible for simultaneous improvements in mechanical and oxidation‐resistant properties. Abstract : Grainsize‐decreased and full‐density ultra‐high‐temperature materials are prepared under extreme condition of ultra‐high pressure. The specimen exhibits excellent mechanical properties (hardness increases 46%, fracture toughness increases 69%) and oxidation resistance (oxidation temperature rises 250 °C). Dislocation multiplication with grain‐refining is proved to dominate the fabrication process, which is responsible for the simultaneous improvements in mechanical and oxidation‐resistant properties.